Turbid Arctic Coastal Waters: Potential Hotspots for Primary Productivity. Riverine Influence on Microbial Productivity in high Arctic Fjords - Andersen, Sebastian D.J. (UiT Norges arktiske universitet, 2022)
The coastal domain of the Arctic is in rapid change with shifts in discharge phenology and catchment characteristics. Riverine discharge shapes hydrography, under water light climate, and nutrient dynamics during the brief melt season. Nutrients transported from catchment to coast can stimulate primary productivity, yet light attenuation caused by high surface turbidity is considered a limiting factor. This in turn affects the relative role of bacterial growth, with subsequent changes to carbon and metabolic balances. However, the effect of nutrient versus light availability on microbial growth remains understudied. The main goal of this master’s thesis was to assess the impact of riverine inputs on bacterial and primary production in a High Arctic Fjord Estuary. A full melt season study (May to September) was conducted in Adventfjorden, Svalbard, with samples collected across horizontal and vertical salinity and turbidity gradients. Microbial productivity was measured using in vitro incubations for net primary productivity (NPP) and bacterial production (BP), using the 14C-bicarbonate and 3H-methyl-thymidine incorporation essay methods. I paired this with in situ estimations of system metabolic balance (gross community production (GCP) versus community respiration (CR)) over a 24h incubation period. I found that NPP had the potential of exceeding BP by 100 to ~2800 times in freshwater influenced fjord waters, which was up to 3 times higher than the saline fjord max. Light had a strong impact on system metabolic balance, yet the system was net autotrophic even under low light conditions. River influenced areas in Arctic fjords are potential hotspots for high, sustained primary productivity during the melt season, challenging previous consensus. This has implications for our general understanding of nutrient cycling and carbon balances in the Arctic.